2021
DOI: 10.1021/acs.energyfuels.1c03243
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Enhanced Oxidative Thermal Stability of Nanoparticle Organic Hybrid Materials Developed for Carbon Capture and Energy Storage

Abstract: As a result of the growing need for direct air capture (DAC) and integrated carbon capture and conversion technologies, CO2 capture materials that can withstand a wide range of environmental conditions, including fluctuating ambient temperatures and high concentrations of oxidizing agents (i.e., oxygen and moisture), are critically needed. Liquid-like nanoparticle organic hybrid materials (NOHMs) have been proposed as candidates for DAC and electrolyte additives, enabling sustainable energy storage (i.e., inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 98 publications
0
26
0
Order By: Relevance
“…Many types of polymers have been shown to be sensitive to thermal degradation in the presence of oxygen. [ 39,41,64,68 ] These results suggest that the presence of oxygen has a significant impact on the degradation behaviors of covalently tethered polymers, while the ionically tethered polymers were much more resistant to oxidative degradation. In our previous work, we showed that the ionic tethering of the HPE canopy to SiO 2 nanoparticles in a higher grafting density and liquid‐like NOHM‐I‐HPE lead to a significant enhancement in the oxidative thermal stability of HPE due to ionic bond stabilization of the N‐terminus and a mass transfer limitation of oxygen.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Many types of polymers have been shown to be sensitive to thermal degradation in the presence of oxygen. [ 39,41,64,68 ] These results suggest that the presence of oxygen has a significant impact on the degradation behaviors of covalently tethered polymers, while the ionically tethered polymers were much more resistant to oxidative degradation. In our previous work, we showed that the ionic tethering of the HPE canopy to SiO 2 nanoparticles in a higher grafting density and liquid‐like NOHM‐I‐HPE lead to a significant enhancement in the oxidative thermal stability of HPE due to ionic bond stabilization of the N‐terminus and a mass transfer limitation of oxygen.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, the crystallization temperature of the NOHMs was shifted by ≈20–25 °C to lower temperatures, suggesting that the HPE confinement suppressed its crystallization, as has been reported in the literature. [ 41,57 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations